Automation of ISP 51 Spectrograph by NI LabVIEW and digital camera - Ghazaryan, D.; Dadayan, T.
In this project, the ISP 51 (Inductively Coupled Plasma) automation was implemented to perform digital calculations. For this, a digital camera was placed in the spectrograph detection area, and all the images obtained were processed using the LabVIEW software environment.
Keywords: Physics